Hodnocení investičního záměru firmy RMA a.s. - Odvárková, Aneta (Vysoké učení technické v Brně. Fakulta podnikatelská, 2013)
Diplomová práce je zaměřena na pořízení vodorovné vyvrtávačky pro společnost, která působí ve strojírenském průmyslu. Informuje o finanční situaci společnosti, srovnává určité nabídky bankovních institucí a leasingových společností a metody hodnocení investičního záměru. Podstatou práce je vyhodnocení konkrétního investičního záměru včetně formulovaní doporučení pro jeho realizaci.

The Master’s thesis is focused on purchase of a horizontal boring machine for a company, which operates in the engineering industry. It informs about the financial situation of the company, compares offers of individual banks and leasing companies as well as methods of evaluation of the investment project. The essential part of the work comprises an evaluation of a specific investment project, including formulation of recommendations for its implementation.
Evaluation of Investment Plan of RMA a.s.
Keywords: Zdroje financování; nákup za vlastní peněžní prostředky; úvěr; leasing; finanční analýza; efektivnost investice; analýza citlivosti.; Sources of financing; purchase using own financial resources; bank credit/loan; leasing; financial analysis; efficiency of investments; sensitivity analysis.